Remoção de cromo trivalente e hexavalente empregando partículas de sericina-alginato como bioadsorvente alternativo - Andrade, Júlia Resende de (2016)
Adsorption is acknowledged as an effective and economical method in the treatment of effluents containing toxic metals. The utilization of bioadsorbents is promising and advantageous, due to the low cost and high availability of these materials, including sericin-alginate particles. This work aims the evaluation of trivalent and hexavalent chromium bioadsorption onto sericin-alginate particles. To reach this goal, kinetic tests were performed to verify the effects of metal solution initial concentration and contact time. The kinetic models of pseudo-first order, pseudo-second order, Elovich, intraparticle diffusion, Boyd and external film mass transfer were adjusted to experimental data. The results indicated distinct mechanisms involved in Cr(III) and Cr(VI) removal, being the latter related to the adsorption-coupled reduction. Thereafter, Cr(III) and Cr(VI) bioadsorption equilibrium studies were carried out. The isotherms obtained at different temperatures were tested by Langmuir, Freundlich and Dubinin?Radushkevich models. Maximum bioadsorption capacity obtained from the fitting of Langmuir model at 40 °C was approximately 0.101 mmol.g-1 for Cr(III) and 0.888 mmol.g-1 for Cr(VI). From the Langmuir equilibrium constant, the thermodynamic parameters enthalpy change, entropy change, and Gibbs free energy change were calculated, being verified the spontaneous and exothermic nature of bioadsorption processes of chromium ions. This work also involved the sericin-alginate particles characterization before and after Cr(III) and Cr(VI) bioadsorption. The following techniques were employed: N2 physisorption, helium pycnometry, mercury porosimetry, optical microscopy, scanning electron microscopy, infrared spectroscopy, X-ray diffraction and thermic analyses. No significant modifications were verified in the properties of sericin-alginate particles after contamination with chromium ions. In the end, the results showed that sericin-alginate particles constitute a promising bioadsorbent material for the effective removal of ions Cr(III) and Cr(VI) from aqueous solutions.